Unhealthy Lifestyle and the Prevalence of High Blood Pressure Among Early Adults: a Cross-Sectional Study - Wahyudi, Andri Setiya; Maulidiyah, Faizah; Suarilah, Ira; Sukartini, Tintin; Pratiwi, Ika Nur (International Journal of Psychosocial Rehabilitation, 2020)
Younger people with an unhealthy lifestyle have been predicted to have factors related to the risk of hypertension. To determine the factors that contribute to the risk of hypertension in early adults, a cross-sectional descriptive correlational study was conducted from 393 of eligible early adults by cluster sampling techniques. The independent variables were nutrients, sleep, smoking, and anxiety. The dependent variable was blood pressure. The nutrient was measured by BMI, sleep was assessed by the quantity of sleep in hours per day, smoking was measured by the Global Tobacco Surveillance System (GTTS), and Hamilton Rating Scale for Anxiety (HARS) was used to measure anxiety. The contributing factors were analyzed by chi square with α ≤ .05. 58.27% of participants experiencing obesity, 45.30% less sleep, 66.41% smoked in moderate levels, 56.49% of them expressed anxiety, and 60.05% showed high blood pressure. The association between all variable and blood pressure were: nutrients (p =